Metode Interpolasi Newton dengan Selisih Terbagi Menggunakan Python dan Excel: Studi Efisiensi dan Visualisasi - Meita Rehania; Ratih Irmawanti; Ari Wibowo (Pendidikan Matematika FKIP Universitas Mataram, 2026)
Interpolation is one of the numerical methods used to estimate the value of a function between known data points. One commonly used technique is Newton's divided difference method. This study aims to explore the implementation of this method using two applications, namely Microsoft Excel and Python, and to compare their accuracy, efficiency, and ease of use. The method employed is a descriptive quantitative case study with data consisting of four points (x, f(x)), and it calculates the approximate function value at the point x=2.5. The calculations were performed manually in Excel and automatically through a Python script. The results show that both applications produced the same interpolation value, f(2.5) = 13.3125, with zero error. The graphical visualization in both applications also aids in understanding the function's approximation. Excel is rated superior in ease of use and initial visualization, while Python is more flexible for processing large-scale data and automation. This study recommends the complementary use of both learning and advanced numerical analysis.